Variationer av klor, svavel och aska i havrekärna : odlingsfaktorernas inverkan på havrens bränsleegenskaper - Larsson, Martin (SLU/Dept. of Soil Sciences, 2007)
The increasing oil prices during the last years have made it profitable to use cereal grains as a fuel. When compared with wood, cereals contain higher amounts of Cl, S and ash. The Cl and S content makes the gases from cereal combustion more corrosive than gases from wood combustion. The goal of this master thesis was to find out the variation of Cl, S and ash content for oat grain grown under different conditions. Oats was chosen because in Sweden it's considered as the cereal with the best fuel qualities. The cultivation factors given most attention were S and Cl supplied by fertilisers. Attention has also been given to soil type, soil pH and S and Cl deposition.